Gut microbiota characteristics in neonatal respiratory distress syndrome and the therapeutic potential of probiotics in recovery - Fu, Yongcheng; Wang, Xiujuan; Nie, Lintao; Wang, Zhaorui; Ma, Xiao; Wu, Lijia; Han, Liping; Fu, Wenjun; Wang, Ruoming; Ren, Hongyan; Zhang, Da; Ding, Juan (Frontiers in Microbiology, 2025)
BackgroundNeonatal Respiratory Distress Syndrome (NRDS) is a common and severe respiratory disorder in neonates, particularly among preterm infants (PTIs), and is often associated with hypoxemia and multiple organ dysfunction. This study aims to investigate the gut microbiota characteristics in NRDS and the potential regulatory role of probiotics in restoring gut microbiota dysbiosis.MethodsThis study enrolled 55 PTIs diagnosed with NRDS and 26 preterm infants without NRDS. The NRDS group was classified into two groups based on treatment: an antibiotic-only group (TA group, N = 30) and an antibiotic plus probiotics group (TB group, N = 25). Fecal samples were collected within 48 h of birth and again after recovery, for 16S rRNA sequencing.ResultsThe study revealed that the gut microbiota diversity in the NRDS group was significantly greater than in the non-NRDS group, and the microbiota composition in the NRDS group was closely associated with multiple clinical indicators, including Apgar score, pH, PaO2, and PaCO2. Notably, the abundance of bacteria such as Muribaculaceae Incertae Sedis, Rhodococcus, and Corynebacterium was significantly higher in the NRDS group, which may contribute to disease progression. ROC analysis suggested that gut microbiota could serve as potential biomarkers for diagnosing NRDS. Probiotic intervention notably restored the gut microbiota structure in the NRDS group, particularly by enhancing the abundance of beneficial genera such as Streptococcus, Bifidobacterium, and Clostridium. This intervention reduced the microbiota disparity between the NRDS group and normal one-month-old children, thereby slowing disease progression.ConclusionThis study demonstrated that the NRDS displayed an increase in gut microbiota diversity and alterations in specific bacterial populations, both of which were closely correlated with clinical data. Probiotic treatment aids in restoring the disrupted gut microbiota in NRDS infants, promoting disease recovery, and providing new biomarkers and clinical strategies for managing NRDS.